Engaging stakeholders in contested urban heritage planning and management. (March 2022) - Liu, Yang; Jin, Xin; Dupre, Karine
Abstract: Urban heritage anchors the identity and culture of cities and is a key element in the development of a sense of place. However, when cities experience socio-spatial transformation, urban heritage may be demolished, particularly in historic urban neighbourhoods. Owing to conflicting claims, representations, and discourse, urban heritage often becomes contested—a situation that is usually approached through the engagement of stakeholders in a collaborative planning process. The Dongguan Street precinct in Dalian, China, is an abandoned historical neighbourhood that was scheduled for redevelopment but is now being considered for a level of preservation. It represents an excellent example of contested urban heritage, which will be explored in this research. Through analysis of Dongguan Street stakeholders' perceptions, interests, roles, and interactions in the heritage planning process, the various issues and opportunities pertaining to stakeholder engagement were identified. Strategies are presented to mitigate stakeholder conflicts and support the collaborative planning of urban heritage. The results expand the understanding of stakeholder engagement in contested urban heritage planning and management. Highlights: Different understanding of heritage value is a root of stakeholder conflict in contested urban heritage management. Power disparity is a primary factor that leads to stakeholders' negative attitudes towards their engagement. The public sector, local NGOs and professionals play significant brokerage roles in urban heritage planning. Bottom-up approaches are essential to engage stakeholders in contested urban heritage planning and management.